PROFIL PASIEN YANG MENGALAMI INTERUPSI RADIASI DI INSTALASI RADIOTERAPI RS UNAND TAHUN 2019-2020 - Fila, Aghnia; Hanum, Fathiya Juwita; Hamdani, Rita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: A radiation interruption is a pause during radiation therapy, which is accumulated from the radiation treatment time minus the planned radiation time, Radiation interruption is a fairly common problem even in developed countries. If left unchecked will have a negative impact on the results o) therapy. Purpose: purpose of this study was to determine the, profile of patients who experienced radiation interruptions in radiotherapy at Unand Hospilal in 2019-2020. Methods: The design odf this research s descriptive retrospective. This research took place, from March 2022 to April 2022 at the Radiotherapy Installation of Unand Padang Hospital in 2022. The sampling technique in this study was total sampling. Results: The results of this study showed that as many as 331 people experienced radiation interruptions at the Radiotherapy Installation of Unand Padang Hospital in 2019-2020 with a percentage (40.3%), the highest cause was non-medical problems (68.0%), the highest number of events was at the age of 46- 55 years (27.6%), the most gender is female (70.9%), the most cancer location is in the thoracic region (46.9%) with the highest percentage is breast (43.9%), the most stage is stage IV (28.5%), the highest education level is SMA (41.6%). the patient's occupation is mostly housewives (43.3%), and the highest place of domicile is West Sumatra Province (83.2%). , with the highest incidence being in the city Padang (39.6%). Conclusion: The percentage of radiation interruption patients at Unand Hospital in 2019-2020 was 40.3%. The most common causes of radiation interruptions are non-medical problems. The highest age group for radiation interruption patients is in the 46-55 year age range. More radiation interruptions are experienced by women. The location of most cancers is in the thoracie region with the highest percentage being the breast. From the available stadium data, the stadium that experienced the most radiation interruptions was stadium IV. The highest level of education is high school. The occupation of most patients is housewife. Most domiciles are in Padang City, West Sumatra Province